Spirituální inteligence a její vliv na sociální status a úspěch v tržní společnost - Brychtová, Šárka (Univerzita Pardubice, 2011)
This article tries to clear up of a new term, for present little known in the czech literature – spiritual intelligence. And it tries to sketch its relationship with market society and social statute of its members.
Keywords: spiritual intelligence; market economy; social statute